Factors Correlated to Hospital Performance - Aviliana R. Wenas; Suryadi Tatura; Fredrik F. L. G. Langi (Universitas Sam Ratulangi, 2022)
Abstract: In Indonesia, studies on hospital performance are still based on financial performance, meanwhile, performance based on cost, quality, and relative value of service cost is not carried out.Â Moreover, data based on cost and service quality is very difficult to accessed. On the contrary, data of hospital performance, facility type, cost of service, and quality of service are available for the United States region. This study aimed to analyze the relationship between the type of facility, cost of services, and quality of services related to the performance of hospitals in the United States, using secondary data analysis of hospital performance data collected routinely by The Centers for Medicare and Medicaid Services (CMS). Dataset Project was on their page corgis-edu.github.io/corgis/csv/ hospitals. The hospital performance was the dependent variable, meanwhile, the service costs, service quality, and relative value of service costs to the national average were the independent variables. The results showed that most of the variables used as predictors of hospital performance were related to the outcomes even after controlling the other variables. On the contrary, the quality, cost, and relative value of cardiac arrest services did not affect hospital-level service outcomes. Increased costs are not surprisingly associated with a reduced likelihood of achieving higher performance; the size of the decline is not large, namely 1-0.90 or 10%. In conclusions, the type of facilities, service costs, and service quality are related to the hospital performance.Keywords: hospital performance; type of facilities; service costs; service qualityÂ Abstrak: Penelitian kinerja rumah sakit di Indonesia masih mengkaji kinerja berdasarkan kinerja keuangan sedangkan kinerja rumah sakit berdasarkan biaya, kualitas dan nilai relatif biaya layanan masih belum dilakukan. Selain itu, data yang berkaitan dengan biaya dan kualitas layanan masih sangat sulit diakses. Berbeda halnya dengan wilayah Amerika Serikat dimana data kinerja rumah sakit, jenis fasilitas, biaya layanan, dan kualitas layanan telah tersedia. Penelitian ini bertujuan untuk menganalisis hubungan antara jenis fasilitas, biaya layanan, dan kualitas layanan berhubungan dengan kinerja rumah sakit di Amerika Serikat menggunakan data kinerja rumah-rumah sakit yang secara rutin dikumpulkan The Centers for Medicare and Medicaid Services (CMS). Dataset Project terdapat di laman corgis-edu.github.io/corgis/csv/hospitals. Kinerja rumah sakit merupakan variabel dependen dalam analisis sedangkan biaya layanan, kualitas layanan, dan nilai relatif biaya layanan terhadap rerata nasional merupakan variabel independen. Hasil penelitian mendapatkan bahwa sebagian besar variabel penelitian yang digunakan sebagai prediktor kinerja rumah sakit berhubungan bermakna dengan luaran tersebut bahkan setelah pengontrolan variabel lain. Berbeda dengan kualitas layanan, biaya dan nilai relatif biaya layanan serangan jantung yang tidak memengaruhi hasil penilaian kinerja rumah sakit. Peningkatan biaya berhubungan dengan penurunan kemungkinan pencapaian kinerja lebih tinggi; besar penurunannya memang tidak besar, yaitu 1-0,90 atau 10%. Simpulan penelitian ini ialah jenis fasilitas, biaya layanan, dan kualitas layanan berhubungan dengan kinerja rumah sakit.Kata kunci: kinerja rumah sakit; jenis fasilitas; biaya layanan; kualitas layanan